Effect of Storage on The Chemical Quality of Pasteurized Milk with Supplemented Soybean Oil and Phycocyanin - Angela Nitia Nefasa; Ega Zahrotun Nisa; Marcelinus Christwardana (Journal of Bioresources and Environmental Sciences, 2022)
The interaction between the addition of soybean oil and phycocyanin extract on the protein, fat, and solid non-fat content of pasteurized milk after a one-week storage period is highly important to investigate. Soybean oil is used to improve the quality of pasteurized milk, particularly its chemical quality, consisting of fat, protein, and Solid Non-Fat (SNF). Phycocyanin extract provides a source of protein, whereas soybean oil contains healthy fatty acids. Before the fresh milk is pasteurized, soybean oil and phycocyanin are added. The LTLT (Low Temperature Long Time) technique was used to pasteurize the milk at 63 °C for 30 minutes. After the pasteurization procedure was completed, the milk samples were refrigerated for one week at a temperature of 4 °C. Following the storage period, the chemical composition of pasteurized milk is examined. With the addition of soybean oil and phycocyanin extract, the protein content of milk rose, as shown by the findings. The sample T1 with a concentration of 0.45% soybean oil and 0.50% phycocyanin extract had the greatest amount of protein (3.58). The sample T2 with 0.45% soybean oil concentration and phycocyanin extract (1%) had the greatest fat content (6.4%). Adding soybean oil and phycocyanin extract enhanced the total SNF concentration. On the basis of the study conducted, it can be concluded that the addition of soybean oil and phycocyanin extract to pasteurized milk has an influence and interaction on the milk's protein, fat, and SNF content. The addition of soybean oil and phycocyanin extract to pasteurized milk held for one week may boost protein, fat, and SNF concentrations.